Towards a Politics of Restraint.: Public Choice Theory in the Dutch Labour Party of the 1970s. - Kayzel, Thomas (TSEG - The Low Countries Journal of Social and Economic History, 2021)
Public choice theory, an analysis of politics based on economic principles, is often considered to be one of the major innovations in economics and political sciences in the second half of the twentieth century. In its formulation by James Buchanan and Gordon Tullock, public choice is commonly understood as one of the major theoretical building blocks in the development of neoliberal thought. It was also remarkably popular with economists and political scientists within the Dutch Labour Party (Partij van de Arbeid) in the mid-1970s. This latter fact is surprising since public choice was seemingly at odds with the Keynesian ideas around which the Labour Party had built its economic policy. This article investigates why and how public choice became popular in the Labour Party. In understanding the popularity of this theory, I will argue, it is important to see the popularity of neoliberal ideas not only in reaction to the economic tribulation of the period but also as a discussion on social planning and an expression of discontent with the democratization movement. Since the rise of neoliberalism in Dutch policymaking is often understood as coming from liberal and conservative channels, studying public choice within the Labour party will shed new light on the development of neoliberalism in the Netherlands.